PTU-119 Phenotypic Characteristics And Localisation Of Novel Human Liver Infiltrating Nkp46 Subsets. (9th June 2014) - Ming, M; Thomas, C; Jeffery, H; Chen, Y-Y; Adams, DH; Mutimer, DJ; Oo, YH
Abstract : Introduction: CD56 + Natural killer cells are the principal effector cells of the innate immune system and have a well-established role in tumour surveillance and anti-viral immunity. Expression of NKp46 has been shown to correlate closely with the severity of liver inflammation, viral resistance to IFN treatment and the attenuation of liver fibrosis. CD56 + NKp46 cells expressing IL-17 and IL-22 have also been described as a family of innate lymphoid cells in humans. Although the role of intrahepatic NK cells has been well described, little is known about the function and phenotype of intrahepatic NKp46 subsets. Thus, We aim to investigate the phenotypic characteristics of CD56 + NKp46 cells in the inflamed human liver, with a view to exploring their functional role. Methods: Liver infiltrating lymphocytes were freshly isolated from explanted human liver tissue from our transplant program and phenotyped with multicolor flow cytometry. Cellular localization was investigated by immunohistochemistry and confocal microscopy Results: Human liver infiltrating NK cells reside predominantly around biliary epithelial cells at the portal tract close to regulatory T cells. We observed two populations of liver-infiltrating CD3 neg CD19 neg CD56 pos cells distinguished by different levels of NKp46, NKp46 mid (15% ±4.8 SD) and NKp46 high (11% ±1.2 SD) neither subset expressed NKp44. The chemokine receptor expression of NKp46 mid and NKp46 high populations was: CCR6 (12% ± 3 vs. 7%± 2.4), CCR9 (20% ± 5.6 vs. 9% ± 0.9), CX3CR1 (18% ± 14 vs. 10% ± 1) CXCR3 (47%±14.4 vs 38%±11.0) and CXCR6 19% ± 4.0 vs. 14% ± 4.6). Both populations expressed IL-18R (42% ± 5.4 vs 7% ± 1.0), IL-23R (19% ± 6.0 vs. 11% ± 2.5), surface receptor CD161 (61% ± 12.1 vs 85% ±4.8) and the integrin receptor CD103 (4% ± 1.35 vs. 16% ± 1.7). The NKp46 high population was highly enriched with the activation marker CD69 (77%±18%). NKp46 cells were also shown to express TNF-α (29% ± 7.5), IFN-γ (70% ± 7.0), Granzyme B (23% ± 11.0) and Perforin (23% ±11.1) along with transcription factor Tbet (19% ± 9.1). Conclusion: We hereby report novel subsets of liver infiltrating CD56 + NKp46 cells, which localise around the portal tract biliary epithelium in the inflamed human liver. These populations have distinct cytokine, chemokine and CD103 expression, which may explain their recruitment, positioning and effector functions in the inflamed hepatic microenvironment. Disclosure of Interest: None Declared.